MATHEMATICS MODEL IN VITALITY ANALYSIS OF THE LIMOLA LANGUAGE - Aswad A, Muhammad Hajarul; Rusdiansyah, Rusdiansyah; -, Didiharyono; Saputra, Yusril Ihsa; Fadli, Imam (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
One of the regional languages in Tana Luwu, especially in North Luwu Regency, is the Limola language. Limola language is a regional language used in communication by the people of Sassa Village. This research utilizes the Pinasco and Romanelli (PR) model to analyze the vitality of the Limola language. The language's sustainability is assessed through a questionnaire with vitality indicators based on UNESCO. Meanwhile, birth and death rates are derived from statistical data from North Luwu. This research found that the model used can explain the possibility of using the Limola language by taking into the carrying capacity and average birth and death rates of users of the Limola language. There are three conditions found. The third condition, despite the birth and death rates of Limola language users being higher than those of people using other languages, the usage of the Limola language still decreases. This is because the language used to communicate as a child as an indicator of the carrying capacity of the Limola language, is very small. In addition, five out of the nine vitality indicators formulated by UNESCO are endangered, posing a threat to the survival of the Limola language